Ag3VO4 Nanoparticles Decorated Bi2O2CO3 Micro-Flowers: An Efficient Visible-Light-Driven Photocatalyst for the Removal of Toxic Contaminants - Li, Shijie; Hu, Shiwei; Jiang, Wei; Liu, Yu; Liu, Yanping; Zhou, Yingtang; Mo, Liuye; Liu, Jianshe (Frontiers in Chemistry, 2018)
Semiconductor-based photocatalysis is of great potential for tackling the environmental pollution. Herein, a novel hierarchical heterostructure of Bi2O2CO3 micro-flowers in-situ decorated with Ag3VO4 nanoparticles was developed by a facile method. Various characterization techniques have been employed to study the physical and chemical property of the novel catalyst. The novel catalyst was utilized for the photocatalytic removal of industrial dyes (rhodamine B, methyl orange) and tetracycline antibiotic under visible-light irradiation. The results indicated that Ag3VO4/Bi2O2CO3 heterojunctions showed a remarkably enhanced activity, significantly higher than those of bare Ag3VO4, Bi2O2CO3, and the physical mixture of Ag3VO4 and Bi2O2CO3 samples. This could be ascribed to an enhanced visible-light harvesting capacity and effective separation of charge carriers by virtue of the construction of hierarchical Ag3VO4/Bi2O2CO3 heterojunction. Moreover, Ag3VO4/Bi2O2CO3 also possesses an excellent cycling stability. The outstanding performance of Ag3VO4/Bi2O2CO3 in removal of toxic pollutants indicates the potential of Ag3VO4/Bi2O2CO3 in real environmental remediation. Highlights Novel architectures of Ag3VO4 nanoparticles modified Bi2O2CO3 micro-flowers were constructed. Novel Ag3VO4/Bi2O2CO3 exhibited excellent photocatalytic activity and stability. Ag3VO4/Bi2O2CO3 heterojunctions significantly promote the charge separation.